MENINGKATKAN KEMAMPUAN MEMBACA CEPAT SISWA SEKOLAH DASAR - HALIMATUSSAKDIAH .; LAURENSIA MASRI P (Universitas Negeri Medan, 2013)
ABSTRACT The type of the research is Classroom Action Research. This research is aimed to improve grade V students’ fast reading ability by using Speed Reading Method at State Primary School 101800 Deli Tua, Deli Tua Subdistrict, Deli Serdang Regency, Academic Year 2012. Data collecting is done as follow : (1) reading speed test, (2) reading comprehension test, (3) then data improvement is done by through Focus Group Discussion (FGD) with grade V primary school teachers to know the students’ reading obstacles. In pre-cycle test, the students’ achievement result is very low. Class Va is in good category with the average of students’ fast reading is 155 wpm and the reading comprehension ability is 85%. In class Vb, the average of students’ fast reading is 167 wpm and the reading comprehension ability is 86% which is in good category. In cycle II, the improvement of students’ fast reading ability is 76,6%. And the improvement of students’ reading comprehension ability is 76%. It means that the speed reading method can be applied to improve students’ fast reading and reading comprehension ability. Keywords: Fast reading, speed reading method, primary school students